3-DIMENTIONAL MODELING OF CYLINDRICAL CONCRETE UNDER AXIAL COMPRESSION WITH VARIATIONS OF MESH ELEMENT TECHNIC AND EFFECT OF REDUCED INTEGRATION - Wiryadi, I Gede Gegiranang (Jurnal Ilmiah Teknik Sipil, 2021)
Research with numerical methods using computer programs has increased in recent years in various fields including the field of structural materials. However, this numerical analysis still needs to be developed in terms of modeling techniques in order to get the results according to the real condition. In this paper, modeling of concrete-cylinder with numerically method using a finite element based computer program, Abaqus®, presented.. Modeling technique to inventigate the mesh element technique and the reduced integration on hourglass control. Modeling specimen is in the form of cylindrical concrete measuring 150 mm x 300 mm with a quality of 25 MPa. Concrete plastic behavior is modeled with the concrete damage plasticity (CDP) feature. The results of the analysis show that the reduction-integration of hourglass control gives a lower peak load effect when the material passes the elastic limit. Meanwhile, a better mesh technique is to use 8-noded hexahedral because it is more stable and the reduction-integration effect of hourglass control can work.